Pengaruh Pemasaran Digital Terhadap Minat Beli Konsumen: Studi Pada PKM Tabaxain.aja - Nirmala, Della Sevia; Nafiqoh, Anin; Manjasari, Putri Vitaliya; Jiadi, Eka Jenny Maharani Putri; Ningsih, Kristina Diana; Kuswandi (CV ODIS, 2024)
Digital marketing has become a very effective marketing strategy in influencing consumer buying interest. Various digital platforms such as websites, social media, and email allow companies to connect more personally with potential customers. Digital marketing is used to attract more consumers faster, connect with them, promote business brands, build consumer loyalty and increase sales, which ultimately is to increase profits. In this case, to increase profits, continuous communication is carried out and will find the theory of social interaction. The purpose of this study is to find out how much influence digital marketing has on the buying interest of Tabaxain.aja consumers. The methodology used in this analysis uses a quantitative approach with data collection techniques that utilize google forms for filling out questionnaires distributed online. The results of the research data show that digital marketing (X) has significant results on the buying interest of Tabaxain.aja consumers (Y).